Predicting Financial Sustainability in Charities in The Malaysian Environment - Sharon, Cheuk; Esmie, Obrin Nichol; Michael, Tinggi; Salawati, Sahari (UNIMAS Publisher, Universiti Malaysia Sarawak, 2019)
Charity failure has been a problem that has plagued developed countries; it has been attributed to the poor economy and the resulting fall in donation levels, lack of funding, increased competition for funding, lack of administrative capacity, lack of risk management, inadequate resource planning and development, inadequate fiscal controls, failure to set and adhere to best practices, policies, procedures and standards, and theft and embezzlement, amongst others. A good number of governance failures have been noted amongst charities in the Asian region. From the financial perspective, we view charity failure as an impairment of financial sustainability, or financial vulnerability; hence by inference, we propose to investigate accountability, board tenure diversity, revenue diversification, own income generation and financial management capacity as possible factors in predicting financial vulnerability in charities. Lack of sufficient study has been made in this area, hence originality is considered high. The study utilises a panel data regression method to test the hypotheses of the research. The framework proposed is expected to better predict financial sustainability using specific indicators in the Malaysian charity environment and the confirmed and tested model is envisaged to be a precursor for a charity financial sustainability index that can be used to rate/rank charities as well as other non-profit organisations. Such an index can in turn be utilised for deciding on: allocation of government funding, extension of financing by financial institutions, and financial support provision by donors.